The Influence of Multimedia on Grade 7 Social Studies Students’ Motivation in the Maldives - Azra, Mariyam (2023)
The purpose of the study is to examine the influence of multimedia on student’s motivation in grade 7 social studies in the Maldives. It is a case study using qualitative method. The objectives of the study are to identify how multimedia influences students’ motivation in learning, to recognize students' perspectives of using multimedia in learning, identify teachers' perspectives of using multimedia in teaching and to study the multimedia teaching methods that incorporated in the class. One of the primary schools in Male’ involving 20 grade 7 students have been purposefully selected. For focus group interviews, 10 participants who had extensive exposure to learning social studies through multimedia were interviewed, while the remaining 10 participants were selected from a class that rarely uses multimedia. Furthermore, 2 teachers who frequently and rarely use multimedia were used for the observation. Qualitative data was collected through a series of ongoing classroom observations of the teachers and students. Interviews with teachers and students were conducted at the beginning and at the end of the data collection phase. Coding and memo writing were used to evaluate data obtained through in-depth field interviews. The findings of this study indicated that lessons conducted in multimedia presentation are much better than the traditional method. Students’ interest, motivation and participation were reported to have increased using multimedia presentation. On the other hand, traditional instruction had no influence on the students’ academic achievement and motivation. The traditional method had difficulties in grasping abstract topics and thus made learning process harder. The multimedia elements used in the multimedia presentation group caused the students to be attentive and enjoyable (satisfaction) while the use of pictures and text, videos and animations influence motivation and enhanced learning. Students in the multimedia group were more involved in the learning process due to increased class participation. The use of multimedia integrated instructional methods, such as multimedia presentations, games, demonstrations and simulations, helps to improve instruction and motivation towards learning.